Functional and Radiological Outcome of Long Bone Fractures in Children (5-14 Years) Using Flexible Intramedullary Nail (FIN) - Singh, Deepak; Singh, Sukhmin; Moger, Nagaraj Manju; Samanta, Pritam (Asian Journal of Medical Research, 2022)
Background: Treating fractures of long bones in children presents special challenges to the orthopaedic surgeons. In addition to smaller size, the presence of open physis and immature vascular patterns must be considered. Flexible intramedullary nailing (FIN) or titanium elastic nail (TEN) are preferred over conservative and other operative managements like traction, splints/ orthosis, plaster casts, external fixation, and open reduction and internal fixation using plates and screws nails for various long bone fractures in children older than five years. The purpose of the study was to find out clinical, functional and radiological outcome of long bone fractures in children between the age of 5 to 14 years treated using flexible intramedullary nail and report the complications associated with same. Subjects and Methods: A total 40 patients in the age group of 5-14 years with fractures of femur, tibia, humerus and radius/ulna were stabilized using flexible nailing. Clinical and radiological follow-up was done for a period of 3 years from October 2014 to October 2017. The functional results were analysed by using range of motion (ROM) in various joints and limb length and Radiological union was assessed by the identification of bridging callus at 3 cortices on antero-posterior and lateral radiographs. Results: Mean age at surgery was 9.77 years (range 7.29-12.25 years). The mean duration of surgery was 53 (35-90) minutes and the range of duration of hospital stay was 2-20 days. Delayed union (n=2) was the most common complication followed by superficial infection (n=1). 92.5% of cases achieved full range of motion, 82.5% cases were found radiological union within five weeks of operation. Conclusion: Based on our experience and results, we conclude that flexible intramedullary technique (FIN) as a minimal invasive procedure appears to be safe and reliable method that has good long-term results in the treatment of pediatric diaphyseal fractures of long bones in children aged 5-14 years. Early range of motion with bony union is achieved in most of patients but still require studies with larger data to validate the findings of this study.